Clinical management of a ruptured intracranial aneurysm - Trakolis, Leonidas; Petridis, Athanasios K. (Frontiers in Stroke, 2024)
Background: Intracranial hemorrhage due to a ruptured aneurysm is one of the most serious neurosurgical emergencies. The patient mostly presents with severe headaches and neurological deterioration. A rapid diagnosis and an interdisciplinary approach play a major role in the fate of these patients. The treatment can vary from endovascular to surgical and must be carefully and individually planned. Neurovascular expertise and an interdisciplinary approach are of vital importance and obligatory for the best possible outcome. Methods: In this narrative review, we scrutinize the current literature and discuss the actual data and guidelines in order to emphasize the importance of the interdisciplinary expertise and approach in patients with ruptured intracranial aneurysm. Results: The current approach to patients with ruptured aneurysm is inhomogeneous and often ineffective due to internal disputes between different disciplines. Although there is plenty of literature and hard evidence to "show the way", many still choose to base their decisions on personal experience or opinion. Conclusions: Every ruptured brain aneurysm should be approached in an interdisciplinary manor and treated according to the current evidence and guidelines. Διέγραψε: 88 Μετακίνησε (εισαγωγή) [8] Διέγραψε: Nevertheless 89 Διέγραψε: From our point of view, we treat ruptured aneurysms in 90 the first 24 hours if possible. We exclude 91 Διέγραψε: where the 92 Διέγραψε: when the brain comes out of the craniotomy 93 Διέγραψε: On one occasion, we had to drag a patient with aSAH 94 from the coronary angio-suite, since the cardiologist was convinced 95 that a patient with an aSAH needed a coronary stent first.